2020
DOI: 10.1111/ctr.13796
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the INTERMACS profile at the time of assessment for heart transplant

Abstract: The Interagency Registry of Mechanically Assisted Circulatory Support (INTERMACS) profiles are associated with mortality in heart failure patients undergoing ventricular assist device (VAD) implantation and heart transplantation (HTx). We assessed the prognostic value of the INTERMACS profile at the time of assessment for HTx or durable VAD implantation as bridge to candidacy (BTC). A total of 503 consecutive patients considered for HTx or VAD between 2006 and 2016 were included. The associations between INTER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several clinical risk prediction scores have been developed to risk stratify patients with heart failure and evaluate the potential benefit of advanced therapies. The most well recognized are the Seattle Heart Failure Model (SHFM), the Heart Failure Survival Score (HFSS), and the Interagency Registry for Mechanically Assisted Circulatory Support (INTER-MACS) [4,30]. The application of machine learning to clinical registry to predict posttransplant outcomes is an active area of research [31].…”
Section: Prognostic Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical risk prediction scores have been developed to risk stratify patients with heart failure and evaluate the potential benefit of advanced therapies. The most well recognized are the Seattle Heart Failure Model (SHFM), the Heart Failure Survival Score (HFSS), and the Interagency Registry for Mechanically Assisted Circulatory Support (INTER-MACS) [4,30]. The application of machine learning to clinical registry to predict posttransplant outcomes is an active area of research [31].…”
Section: Prognostic Scoresmentioning
confidence: 99%
“…The 2021 European Society of Cardiology Guidelines propose utilizing the INTERMACS profiles to guide early risk stratification for temporary mechanical support and consideration for transplantation [14 ▪▪ ,33]. However, Friesen et al [30] and found no statistically significant association between specific INTERMACS profiles at presentation and composite outcome of mortality or de-listing.…”
Section: Primary Cardiovascular Assessmentmentioning
confidence: 99%
“…This surgical procedure can prolong survival approximately 11 years in end-stage heart failure adult patients [4]; in addition, close to 85% of recipients survive the first year post-HT [5]. There are several factors associated with a poor prognosis in HT recipients, such as mechanical circulatory support [4], history of congenital heart disease, restrictive cardiomyopathy, re-transplantation [4], pre-transplant serum creatinine higher than 2.0 mg/dL [4], pre-transplant total bilirubin higher than 2.0 mg/dL [4], recipient age higher than 55 years old [4], pre-operative clinical instability, defined as Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile I (cardiogenic shock); or profile II (progressive clinical decline despite treatment with inotropes) [6,7]; as well as donor factors, such as advanced donor age and prolonged donor heart ischemia [4]. Even considering these factors, the rate of mortality in HT recipients is high, therefore, determining prognostic markers in these patients will always be helpful in making evidence-based decisions.…”
Section: Introductionmentioning
confidence: 99%